Prevalence of low skeletal muscle mass following bariatric surgery. (June 2022) - Molero, Judith; Olbeyra, Romina; Flores, Lilliam; Jiménez, Amanda; de Hollanda, Ana; Andreu, Alba; Ibarzabal, Ainitze; Moizé, Violeta; Cañizares, Sílvia; Balibrea, José María; Obach, Amadeu; Vidal, Josep
Summary: Background and aims: Evidence on the occurrence of low skeletal muscle mass (low-SMM) following bariatric surgery (BS) as well as on the impact of low-SMM antedating BS on post-surgical body composition (BC) are scant. In this context, we aimed to prospectively evaluate the prevalence of low-SMM prior to and up to 5 years after BS, and to evaluate pre-surgical low-SMM as an independent risk factor for the presence of low-SMM after BS. Methods: Retrospective analysis of prospectively collected database. BC was assessed by bioelectrical impedance analysis (BIA). A BIA-based formula was used to calculate skeletal muscle mass (SMM). Class I and class II low-SMM were defined respectively as a SMM index (SMMI = SMM/height 2 ) value between −1 and −2, or > −2 standard deviations from the gender-specific regression line of the BMI versus the SMMI relationship in our reference group. Results: A total 952 subjects were included, with BC being available for 877 (92%) subjects at 12 months and for 576 subjects (60%) at 60 months after BS. Prior to surgery, and at 12-, or at 60-months after surgery, class I and class II low-SMM was ascertained respectively in 15.6% and 4.6%, 5.3% and 1.4%, and 16.6% and 6.3% of the study participants. Logistic regression analysis showed that the occurrence of low-SMM at 12- and 60-months follow-up, was independently predicted not only by age at the time of surgery [respectively, HR: 1.052 (95% CI 1.020–1.084), p = 0.001; and 1.042 (95% CI 1.019–1.066); p < 0.001] but also by the presence of low-SMM prior to surgery [respectively, HR: 10.717 (95% CI 5.771–19.904), p < 0.001; and 5.718 (95% CI 3.572–9.153); p < 0.001]. Conclusions: Our data suggest that a low-SMM phenotype occurs not only in obesity surgery candidates but also after BS, and that low-SMM prior to surgery is an important risk factor for low-SMM throughout post-surgical follow-up.